ACCURACY OF GRAY SCALE ULTRASOUND IN DIAGNOSIS OF ACUTE APPENDICITIS - Nayab Alia; Irshad Ahmad; Amir Hayat (Journal of University Medical & Dental College, 2013)
ABSTRACT Objective: To evaluate the role of Graded Compression Ultrasonography in the Diagnosis of Acute Appendicitis and its correlation with clinical signs and histopathological findings. Study Design: Observational study. Setting: Department of Radiology and surgery Madina Teaching Hospital, Faisalabad. Duration of study: 12 months from 1ST June 2009 to 30th May 2010. Sample size: 100. Material and Methods All patients examined clinically, lab investigations, ultrasound and observed up to 06 hours.. The accuracy of ultrasonography in the diagnosis of appendicitis was compared with clinical diagnosis, laparotomy findings and histopathological examination reports and statistically analyzed by using SPSS 10 Results: Out of 100 cases that underwent ultrasonography, 65 cases were sonographically positive for appendicitis and 02 cases were appendicular masses. Right iliac fossa tenderness, rebound tenderness and Rovsing’s sign were the cardinal signs. The overall specificity of ultrasound was 89.74% and the sensitivity was 96.72%, positive predictive value is 93.65% and negative predictive value is 94.59%. In the diagnosis of acute appendicitis. Conclusion: Graded compression Ultrasonography is still a useful tool in the diagnosis of acute appendicitis in spite of sophisticated investigations like CT abdomen and laparoscopy; thus, reducing the cost of treatment and improve adverse outcome.